Directed differentiation of rhesus monkey ES cells into pancreatic cell phenotypes - Nauert Brian; Andrews Laura; Kuo Hung-Chih; Lester Linda B; Wolf Don P (Reproductive Biology and Endocrinology, 2004)
Abstract Embryonic stem cells (ES) can self-replicate and differentiate into all cell types including insulin-producing, beta-like cells and could, therefore, be used to treat diabetes mellitus. To date, results of stem cell differentiation into beta cells have been debated, largely due to difficulties in defining the identity of a beta cell. We have recently differentiated non-human primate (rhesus) embryonic stem (rES) cell lines into insulin producing, beta-like cells with the beta cell growth factor, Exendin-4 and using C-peptide as a phenotype marker. Cell development was characterized at each stage by gene and protein expression. Insulin, NKX6.1 and glucagon mRNA were expressed in stage 4 cells but not in early undifferentiated cells. We concluded that rES cells could be differentiated ex vivo to insulin producing cells. These differentiated rES cells could be used to develop a non-human primate model for evaluating cell therapy to treat diabetes. To facilitate the identification of beta-like cells and to track the cells post-transplantation, we have developed a marker gene construct: fusing the human insulin promoter (HIP) to the green fluorescent protein (GFP) gene. This construct was transfected into stage 3 rES derived cells and subsequent GFP expression was identified in C-peptide positive cells, thereby substantiating endogenous insulin production by rES derived cells. Using this GFP detection system, we will enrich our population of insulin producing rES derived cells and track these cells post-transplantation in the non-human primate model.